Dynamics of Citizen Participation in Forming Identity in Forming Citizen Identity - Monica Willyananda (International Journal of Students Education, 2024)
This research aims to investigate the dynamics of citizen participation in shaping citizenship identity through a literature review. The research method employed is a literature review, where data are obtained from previous studies encompassing various sources such as journals, books, and scholarly reports. Thematic data analysis was conducted to identify patterns, trends, and relationships between citizen participation and citizenship identity. The research findings highlight the crucial role of citizen participation in building a strong citizenship identity, while challenges such as opinion polarization and the spread of false information through social media are also identified. In conclusion, through collaborative efforts among the government, civil society, and the private sector, communities can strengthen meaningful citizen participation and reinforce the foundation of an inclusive citizenship identity.